Doing Your Research Project / A Guide for First-Time Researchers in Education and Social Sciences - Bell Judith (Open University Press, 1993)
This book aims to provide you with the tools to do the job, to help you avoid some of the pitfalls and time-wasting false trails that can eat into your time, and to establish good research habits. Preface, Acknowledgements, Introduction, Preparing the Ground, Approaches to Educational Research, Planning the Project, Keeping Records and Making Notes, Reviewing the Literature, Negotiating Access and the Problems of ''Inside'' Research, Selecting Methods of Data Collection, The Analysis of Documentary Evidence, Designing and Administering Questionnaire, Planning and Conducting Interviews, Diaries, Observation Studies, Interpreting the Evidence and Reporting the Findings, Interpretation and Presentation of the Evidence, Writing the Report, Postscript, Bibliography, Index.